Selection of Reservoir Release Location Based on Fish Induced Velocity: A Case of Wudongde Hydropower Station on Jinsha River - Gao Yangyang; Chen Zhuo; Liu Ke; Wang Jie; Cheng Sheng; Zhang Xinyi; Chang Duozi; Feng Jingjie (Renmin Zhujiang)
Hydropower development is one way to efficiently harness the energy of rivers. However, damming limits the upstream reproductive behavior of migratory fish, and fish passage facilities are now an important means of restoring connectivity. Flow velocity is an important factor for fish to perceive the environment and maintain swimming behavior. The reservoir in front of the dam has become a near-hydrostatic environment that significantly changes the river properties. Reduced velocity may make it difficult for fish released into the reservoir area by fish passage facilities to find the flow direction, reducing their migratory success rate. This paper takes the Wudongde reservoir as an example and uses numerical simulation to analyze the characteristics of the flow field in the reservoir at different flow levels. It takes the induced velocity of fish as the threshold value to analyze the river sections in the reservoir affected by the reduced velocity. The results show that the flow velocity in the reservoir area decreases significantly from the end of the reservoir to the front of the dam; the flow velocity in the main reservoir is more homogeneous in the direction of water depth, and the tributary estuaries present non-uniform distribution. Under the conditions of low flow (February), medium flow (May), and high flow (August), a certain range of the river section is below the induced velocity of the fish (0.2 m/s), and the suitable locations for migratory fish stocking are located in the upper part of Wudongde Dam, 102, 96, and 38 km, respectively. The results provide technical references for the selection of release sites for fish passage facilities in high dams and large reservoirs, and are of great significance for the protection of water ecology in the dam-built river reaches.